PROTECTION OF MOTHERHOOD AND CHILDHOOD AS A PRIORITY FOR THE DEVELOPMENT OF HEALTH CARE IN UZBEKISTAN (The Role of Exact Sciences in the Era of Modern Development, 2024)
Taking into account the age-old traditions inherent in our people, and in order to further increase the level of ongoing work to implement a wide range of measures aimed at the deepest awareness and approval in society of the important life value and noble idea "a healthy mother is the basis of a happy family, a happy family is the basis of a prosperous state ”, improving the system of protecting the family, motherhood and childhood, creating an atmosphere of special respect and respect for mothers in society, raising a healthy and harmoniously developed generation, strengthening cooperation between public authorities in the field of public organizations in the development of a strong, healthy and friendly family.